2009
DOI: 10.1136/vr.165.19.570
|View full text |Cite
|
Sign up to set email alerts
|

Abortions in pregnant dairy cows after vaccination with Brucella abortus strain RB51

Abstract: The Rose Bengal test, Wright test and 2-mercaptoethanol test (OIE 2004) on the dams' serum showed negative results at the time of abortion and three to four weeks later. Commercial indirect ELISA kits (SVANOVA Biotech) were used for the detection of antibodies to bovine viral diarrhoea virus (BVDV), and bovine herpesvirus type 1 (BHV-1) in serum, according to the manufacturer's instructions (Kampa and others 2004). Serum samples from the aborted cattle were BVDV antibody-positive at the time of the abortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Studies have confirmed that the live vaccine may cause abortions and premature births in pregnant dairy cows. 32,33 Thus, the burden of prevention lies on raising public awareness and curtailing unsafe practices with regard to raw dairy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the live vaccine may cause abortions and premature births in pregnant dairy cows. 32,33 Thus, the burden of prevention lies on raising public awareness and curtailing unsafe practices with regard to raw dairy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, they showed considerable seropositivity, which was justified by the expectation of the 80% protection that the vaccine gives to herds. The RB51 vaccine sample has been alternatively used in several countries in animals aged over 8 months old or as a booster of B19, demonstrating greater resistance to infection and reducing abortion rates (YAZDI et al, 2009;BASTOS et al, 2012). However, it is still not used in the state.…”
Section: Discussionmentioning
confidence: 99%
“…However, RB51 has some drawbacks. Although less virulent than other vaccine strains and generally safe for use in pregnant cattle (Palmer et al., 1997), RB51 can be abortigenic (Yazdi et al., 2009). Additionally, recent reports have shown that RB51 can be shed in milk of previously-vaccinated cattle and infect humans through the consumption of unpasteurized milk (Cossaboom et al., 2018).…”
Section: Introductionmentioning
confidence: 99%